USING FRIENDLINESS, LANGUAGE, INTEREST, AND PRIOR KNOWLEDGE (FLIP) STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT: THE EIGHTH GRADE SMP NEGERI 29 PEKANBARU - M. Fadhly Abbas; Desi Memberti (Universitas Lancang Kuning, 2018)
This research was based on the students’ problem in reading comprehension of narrative text, especially in generic structure, purpose, language features and vocabulary. The purpose of this research was to improve reading comprehension in narrative text. The design of this research was Classroom Action Research (CAR). This research consisted of five meetings in one cycle. This research conducted on March 2018. Based on the test result, it was found that the average score of cycle was 80, 09. Furthermore, the data about factors that influence the students’ improvement in reading comprehension in narrative text were obtained by interview, observation checklist, and field note. The factors were interested of media, students’ enjoy and fun during learning process and this strategy was easily to comprehend. In conclusion, the use of FLIP strategy can improve students reading comprehension in narrative text.